Evaluation of The Use of The Mobile JKN Application to Improve Outpatient Online Registration at Jampangkulon Hospital - Silvia, Hera; Gunawan, Erix (Green Publisher, 2024)
The Mobile JKN application, a groundbreaking innovation by BPJS Kesehatan, empowers national health insurance participants to conduct various service transactions online, including registering for outpatient treatment at health facilities. Many patients have not taken advantage of the ease of online registration through Mobile JKN because they do not understand how to use it and lack education related to Mobile JKN online registration, so they choose the manual method. This study aimed to evaluate the effectiveness of the Mobile JKN application in boosting online outpatient registration using descriptive qualitative research methods. Through interviews, analysis of primary data on outpatient visits, and a psychosocial educational approach, I act as an education provider to provide knowledge and understanding of using the JKN mobile application. The evaluation revealed that 5% of the socialization of the Mobile JKN application proved successful and effective in increasing online outpatient registration in May 2024. The percentage increase is insignificant because the researcher only conducted socialization in April 2024.